Pengaruh Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Varaibel Intervening Pada Perusahaan Basic Materials Yang Terdaftar di BEI Tahun 2020-2024 - Dheandra Asyfa; Jhon Veri; Putri Nadia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of Capital Structure and Profitability on Firm Value, with Dividend Policy as an intervening variable in Basic Materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used was purposive sampling, resulting in a sample of 23 companies from a population of 109 firms over five years of observation. The data analysis methods employed were panel data regression and path analysis, using EViews 13 software.The results indicate that Capital Structure has an effect on Dividend Policy, while Profitability does not affect Dividend Policy. Furthermore, Capital Structure affects Firm Value, whereas Profitability does not affect Firm Value, and Dividend Policy does not affect Firm Value. In addition, the path analysis results show that Capital Structure does not affect Firm Value through Dividend Policy as an intervening variable, and P Brofitability also does not affect Firm Value through Dividend Policy as an intervening variable.